Relationship of Thermal Regulation Capacity of Chicks with Breeder age, Breed and Incubator type - Oro , Camila S.; Souza, Felipe E. De; Rodrigues, Wellyton C.; Milbradt, Elisane L.; Guirro, Erica C.B.P.; Oro, Juliana S. (International Journal of Poultry Science, 2019)
Background and Objective: In chickens, development of the thermoregulatory system during incubation can increase thermal regulation efficiency after hatching and is critical to ensure animal welfare. Several factors, including breeder age, incubator type and breed can all affect thermoregulatory system development. This study evaluated how these factors are related to thermoregulatory system development and how they affect thermal regulation capacity of chicks. Materials and Methods: The experimental design was completely randomized, totaling 12 treatments with 6 replicates each. Each cart inside an incubator served as an experimental unit that contained 5,040 eggs and each type of incubator contained 36 carts. The eggs were derived from Cobb 500 and Ross breeds at three different ages. Results: Chicks produced by young Ross breeders and old Cobb breeders had a lower capacity to remain warm when incubated in a multiple stage incubator and while in the dispatch room. Conclusion: Breed type and breeder age can affect thermoregulatory system development of chicks. A comfortable ambient temperature is needed to ensure appropriate development of chicks.